Implementation of Problem Based Learning to Improve Students Motivation - Rediyono (Jurnal Penelitian Pendidikan IPA, 2025)
The purpose of this study was to describe the implementation of the Problem Based Learning (PBL) learning model with interactive multimedia media and to increase student learning motivation through the application of the Problem-Based Learning (PBL) learning model assisted by interactive multimedia media at SDN Jatisari 3 Bekasi. The research method used is Action Research by adopting the STAR approach (Situation, Challenge, Action, Reflection of Results and Impact). Data were collected through teacher reflection journals, video recordings of learning, observation sheets by school supervisors, interviews with students and teachers, surveys to students, and artifacts of student learning outcomes. The results of this study are that this innovative approach has a significant positive impact on student learning motivation in Elementary Schools. Some of the main findings that can be used as the main conclusions include: increased Student Engagement; interactive multimedia can be an effective tool to facilitate conceptual understanding; improving technological infrastructure is key to ensuring smooth implementation and a smooth learning experience; students find it more fun to learn with multimedia and feel more interested; increased student motivation and participation through the PBL Learning model assisted by interactive multimedia has succeeded in stimulating student learning motivation; and indicators of successful implementation have been met.